Sectoral linkages and carbon leakage: A multi-stage hypothetical extraction analysis of export-embodied emissions - Unal, Emre; Erkok, Banu (Springernature, 2026)
This study investigates T & uuml;rkiye's export-embodied CO2 emissions and efficiency using an environmentally extended input-output framework and the Multi-Stage Hypothetical Extraction Method. The analysis focuses on major partners: France, Germany, Iraq, Italy, the UK, and the US. By decomposing exports into intermediate and final goods and disaggregating final demand into household, government, and investment channels, the research traces emissions along domestic production stages. The results reveal a systemic deterioration in CO2 efficiency across most destinations. While intermediate goods typically dominate the emissions profile, the UK exhibits a broad reliance on both intermediate and final goods. Furthermore, efficiency responses are partner-specific; state-procured government expenditures drive intense liabilities in France and Italy via petroleum and chemical sectors, while acting as deep systemic dependencies in Iraq and the US within utility and heavy manufacturing sectors. Findings document a highly concentrated structure where textiles, transport equipment, petroleum-chemical products, and electricity and gas provisions account for the dominant shares of efficiency effects. This evidence underscores the necessity for targeted, partner-specific industrial policies and technological investments to mitigate carbon leakage and enhance environmental performance in these key economic sectors.
Keywords: Co Emissions; Hypothetical Extraction Method; Input-Output Analysis; C67; O44; Q56